Surges and instability: The maturity shortening channel - Xiang Li; Dan Su (Halle Institute for Economic Research (IWH), 2022)
Capital inflow surges destabilise the economy through a maturity shortening mechanism. The underlying reason is that firms have incentives to redeem their debt on demand to accommodate the potential liquidity needs of global investors, which makes international borrowing endogenously fragile. Based on a theoretical model and empirical evidence at both the firm and macro levels, our main findings are twofold. First, a significant association exists between surges and shortened corporate debt maturity, especially for firms with foreign bank relationships and higher redeployability. Second, the probability of a crisis following surges with a flattened yield curve is significantly higher than that following surges without one. Our study suggests that debt maturity is the key to understand the financial instability consequences of capital inflow bonanzas.
Keywords: F32; F34; F38; F65; G32; 330; capital inflow surges; corporate maturity structure; systemic financial crisis; term structure